Data-driven decision support in the design and controlling of systems engineering transformation: a maturity model - Graessler, Iris; Grewe, Benedikt; Felgen, Luc (Proceedings of the Design Society)
ABSTRACT: Challenges of increasing system complexity and the need for interdisciplinary collaboration are prompting companies to reorganize towards Systems Engineering (SE). As part of the implementation of large-scale transformation programs, transformation progress is of great interest to management and employees involved. Existing maturity models lack measurable variables and reliable forecast. For this reason, a maturity model for evaluating SE Transformation is developed, that builds on quantitative metrics and enables an overarching view on transformation considering cultural aspects. Literature-based criteria for evaluating SE Transformation lay the foundation for measures and referenced metrics and indicators. Due to its data-centricity, the model presented enables a more comprehensive, fact-based decision-making basis for the design and steering of SE Transformation programs.

SETup automotive: a Method for Systems Engineering Transformation in automotive industry - Graessler, Iris; Grewe, Benedikt (Design Science)
Abstract The increasing prevalence of embedded software in today’s vehicles is leading to growing complexity, which can only be managed effectively through the use of reliable interdisciplinary engineering processes. With this in mind, systems engineering (SE) is currently being introduced on a large scale into the automotive industry. Pilot projects have demonstrated the potential for implementing changes, but these have not yet been accompanied by viable implementation concepts for SE. In the context of the proposed application-based research, the SETup automotive method ( S ystems E ngineering T ransformation u nder p iloting in the automotive industry) is presented, which comprises a step-by-step procedure of introducing SE into large automotive companies. By introducing SE by pilot projects first, both an in-process tailoring of all processes, methods, tools and structures (PMTS) required for the introduction and an in-process validation of the pilot scheme elaborated by the pilot projects are achieved. The presented method builds upon fundamental approaches to change management, which have been developed over many years in both research and practice. It has been validated by the industrial practice of SE transformation at German car manufacturers and suppliers. As a result, decision-makers, transformation managers and systems engineers are provided with a scientifically based and field-tested set of steps for the introduction of SE in their own company.

Strategic Product Planning Model – Digital twins for circular products and production processes - Gräßler, Iris; Rarbach, Sven; Grewe, Benedikt (Industry 4.0 Science)

Model-based Impact Analysis for Engineering Sustainable Products in Value Creation Networks - Gräßler, Iris; Rarbach, Sven (Procedia CIRP)

Structuring Systems Engineering Transformation: A three-step cycle of Transformation - Gräßler, Iris; Grewe, Benedikt (Procedia CIRP)

Why I declare a conflict of interest and you should not - Acem, Ensar; Aczel, Balazs; Albayrak, Nihan; Brown, Nicholas J. L.; Dudda, Leonie A.; Elsherif, Mahmoud Medhat; Gjoneska, Biljana; Kowal, Marta; Krishna, Anand; Miłkoś, Szymon; Paruzel-Czachura, Mariola; Patel, Jay; et al. (Theory and Society)
Academic publishing is both an indication of scientific contribution and a currency for career advancement. This dual role gives rise to a normative scientific conflict: Does the structural incentive to publish constitute a conflict of interest (COI) that ought to be disclosed? In this paper, we address this conflict through an action research approach, engaging collaboratively and reflexively to answer four related questions: (1) What evidence suggests that researchers face a (financial) COI when publishing? (2) What are the benefits and drawbacks of explicitly acknowledging that publications function as academic currency? (3) How should such conflicts be disclosed? (4) Do mechanisms such as pre-registration and registered reports resolve these concerns? This paper contends that while researchers are clearly incentivised to publish, this interest need not necessarily constitute a conflict or be explicitly disclosed. Treating this issue as a normative scientific conflict does reveal the need for a shift in how researchers understand and navigate the subjective, self-interested dimensions of their work. We propose four key responses: (1) integrating discussions of COIs and biases more extensively into undergraduate science education, (2) promoting greater reflexivity in everyday research practice (e.g., through reflexivity journals, peer-led audit groups, and the reintegration of discussions on the historicity and cultural nature of research into scientific publications), (3) critically investigating institutional incentives and journal policies, and (4) proactively adopting methodological safeguards such as pre-registration. By addressing this conflict through action research, we demonstrate how normative tensions in science can be made productive — supporting both critical reflection and structural improvement.

Evolving Design for Assembly, Disassembly and Reassembly into a new paradigm: Design-for-Capabilities with Hybrid Decision Support as an enabler for circular products - Gräßler, Iris; Pottebaum, Jens; Nyhuis, Peter; Schmidt, Matthias; Grewe, Benedikt; Vollenkemper, Felix; Hesse, Thomas; Meinecke, Tim (Stuttgarter Symposium für Produktentwicklung (SSP) 2025)

Stages of Systems Engineering: An Analysis and Characterization of Systems Engineering Approaches - Gräßler, Iris; Grewe, Benedikt (Systems)
In the engineering of complex technical systems, Systems Engineering (SE) is a key approach that is becoming increasingly relevant in more and more industries due to the ever-increasing complexity of systems. Over the decades of practical application and research, various specializations and forms of the Systems Engineering approach have developed, but there has so far been a lack of an overarching context and positioning in meaningful stages for the introduction of Systems Engineering in companies. For this reason, this research will systematize common Systems Engineering approaches and bring them together in a stage model for Systems Engineering. Based on a systematic literature review, use cases are identified for each approach and stage, which support companies in selecting an approach suitable for their own organization.
Keywords: Systems Engineering Transformation; maturity; Systems Engineering stages; approaches; SE

Towards Frame-level Quality Predictions of Synthetic Speech - Kuhlmann, Michael; Seebauer, Fritz; Wagner, Petra; Häb-Umbach, Reinhold (Interspeech 2025)

Analyse und Modellierung eines induktiven Ortungsprozesses unter Berücksichtigung der elektromagnetischen Wechselwirkungen planarer Spulensysteme - Lange, Sven
Diese Dissertation befasst sich mit der Entwicklung eines induktiv-basierten Lokalisierungsverfahrens mittels planarer Spulen, das auf magnetischer Kopplung beruht. Grundlage ist die elektromagnetische Induktion, bei der sich die entstehende Spannung proportional zur Gegeninduktivität verhält. Das Verfahren arbeitet im physikalischen Nahfeld und im Frequenzbereich von einigen kHz bis MHz, um eine effiziente Kopplung ohne Ausbreitung elektromagnetischer Wellen zu gewährleisten. Im Vergleich zu etablierten Verfahren wie GPS oder Ultraschall zeigt die induktive Ortung Vorteile bei kurzer Reichweite, insbesondere durch hohe Genauigkeit im Zentimeterbereich und geringe Materialabhängigkeit. Zudem lässt sie sich in bestehende Technologien wie bei der drahtlosen Energieübertragung integrieren und durch Sensorfusion mit anderen Verfahren kombinieren. Zur Modellierung und Optimierung werden physikalische Eigenschaften von planaren Spulen und EM-Feldern analysiert und elektrische Ersatzschaltbilder eingesetzt. Die geometriebasierte Berechnung der Gegeninduktivität ermöglicht die Entwicklung und Bewertung geeigneter Ortungsalgorithmen. Stochastische Filterverfahren verbessern zusätzlich die Robustheit gegenüber Umgebungseinflüssen. Abschließend wird eine modulare Simulationsplattform vorgestellt, die als Grundlage für die Generierung von Trainingsdaten sowie zur Weiterentwicklung von Mess-, Ortungs- und Filtermethoden dient.

From simulation to metamodel to experiment: Evaluating the prediction accuracy of polynomial regression models for clinch joint properties - Einwag, Jonathan-Markus; Steinfelder, Christian; Wartzack, Sandro; Brosius, Alexander; Goetz, Stefan (Journal of Manufacturing Processes)

Surface functionalisation of additively manufactured AlSi10Mg by organophosphonic acid and PDMS grafting - Prüßner, Tim; Hoyer, Kay-Peter; Buitkamp, Nadine; Vieth, Pascal; Grundmeier, Guido (Materials Chemistry and Physics)

Das Linguistic Soundscaping im Elementarbereich. Ein methodischer Ansatz für die Erfahrung von sprachlicher und sprachbezogener Heterogenität. - Varga, Eva (Diskurse und Praktiken der Heterogenität. Pädagogisches Handeln in heterogenen Settings. Mit einem Fokus auf die Elementar- und Primarbildung.)

Innovation Hubs und ihre Lernpotenziale für Auszubildende im Rahmen von BBNE - Schlömer, Tobias; Kiepe, Karina (Innovation für Nachhaltigkeit durch berufs- und wirtschaftspädagogische Forschung)

Paragraphen und Künstliche Intelligenz meistern: Welche Steuerprofis Unternehmen suchen. - Giese, Henning; Schulz, Kim Alina; Sureth-Sloane, Caren (Frankfurter Allgemeine Zeitung)

Zum Schreiben mit der Hand - Kokew, Stephan Matthias

Graphical AI workflow modelling: Identifying relevant competencies in AI-based automation of business processes - Gräßler, Iris; Özcan, Deniz (AHFE International)
This research investigates how Artificial Intelligence (AI) can be systematically integrated into existing business processes by combining suitable competencies with graphical AI workflow modelling. While AI offers a high potential for automation and increased efficiency, its implementation often fails due to a lack of interdisciplinary competencies that bridge the gap between domain expertise and IT know-how. Low-code platforms and visual modelling tools are increasingly recognised as enablers, empowering non-programmers to intuitively create graphical AI- based workflows. Nevertheless, specific competencies are required to realise the full potential of AI, the domain specific knowledge and align technical understanding with AI capabilities. The paper reviews the state of the art in AI-driven business process automation and competencies for visual low-code approaches. It then presents a practical solution to identify and systematise essential competence areas. Based on this, a practical competence model is developed to support the design of user-friendly, AI-enabled workflows. This is tested in a practical application context — emergency management — where it supports critical decision-making processes and is validated through expert feedback. The study concludes by offering actionable recommendations to help organisations foster the necessary competencies and methods for competently integrating AI into their digital processes.

Automation 2035 - Gräßler, Iris; Özcan, Deniz; Tusek, Alena Marie; Bilgic, Attila; Lange, Christian; Stich, Christian; Maul, Christine; Heizmann, Michael; Weyrich, Michael; Dessel,, Sascha; Miny, Torben; Jumar, Ulrich
Executive summary Die vorliegende Zukunftsstudie „Automation 2035“ gibt einen Ausblick auf die Entwicklung der Automatisierungstechnik in den nächsten 10 Jahren. Neben der Beschreibung von Trends wie Kreislaufwirtschaft, Automatisierung der Märkte, Biologisierung, autonome Systeme und Robotik sowie IT-Sicherheit wird die zu erwartende Veränderung in der Bildung beschrieben. Dazu verwenden wir Methoden der Zukunftsforschung und arbeiten mit der Szenarientechnik, um Zukunftsperspektiven der Automation aufzuzeigen. Personas werden eingesetzt, um die zukünftigen Entwicklungen plastisch aus den Augen der Personen im Jahr 2025 und in der Zukunft im Jahr 2035 zu beschreiben. Schlüsselthemen und Trends: ... ... Inhalt Executive summary 1 1 Einführung 3 2 Zukunftsfelder für die Automatisierungstechnik 2035 4 2.1 Kreislaufwirtschaft 4 2.2 Automatisierung der Märkte 7 2.3 Biologisierung 8 2.4 Autonome Systeme und Robotik 10 2.5 Security 12 2.6 Veränderung der Ausbildung 13 3 Szenario der Automation 2035 16 4 Personas 18 4.1 Unternehmer 18 4.2 Ingenieurin 19 4.3 Schüler 20 5 Thesen und Ausblick 22 Methodik 24 Autorenteam 25 Schrifttum 26...

CRC: Compressed Reservoir Computing on FPGA via Joint HSIC LASSO-based Pruning and Quantization - Jafari, Atousa; Ghasemzadeh Mohammadi, Hassan; Platzner, Marco (WiPiEC Journal - Works in Progress in Embedded Computing Journal)
While reservoir computing (RC) networks offer advantages over traditional recurrent neural net- works in terms of training time and operational cost for time-series applications, deploying them on edge devices still presents significant challenges due to re- source constraints. Network compression, i.e., pruning and quantization, are thus of utmost importance. We propose a Compressed Reservoir Computing (CRC) framework that integrates advanced pruning and quantization techniques to optimize throughput, latency, energy efficiency, and resource utilization for FPGA- based RC accelerators.We describe the framework with a focus on HSIC LASSO as a novel pruning method that can capture non-linear dependencies between neurons. We validate our framework with time series classification and regression tasks, for which we generate FPGA accelerators. The accelerators achieve a very high throughput of up to 188 Megasamples/s with a latency of 5.32 ns, while reducing resource utilization by 12× and lowering the energy by 10× compared to a baseline hardware implementation, without compromising accuracy.

Ultra-Low Latency and Extreme-Throughput Echo State Neural Networks on FPGA - Jafari, Atousa; Platzner, Marco (Lecture Notes in Computer Science)